Industry alignment in Japanese language vocational training in Indonesia - Nur Septhalny Isnainun; Budiyono Budiyono; Amin Yusuf (Universitas Negeri Semarang, 2025)
This study assesses the effectiveness of Japanese language training programmes within Indonesia’s vocational education system, with a focus on their alignment with labour market demands. As Japan faces workforce shortages, Indonesia has developed vocational language training to prepare candidates for employment abroad. Despite these initiatives, many programmes still prioritise grammar-based instruction over communicative and cultural competence. A descriptive, quantitative approach, utilising Likert-scale questionnaires, was complemented by semi-structured interviews and document analysis. The results indicate that, while institutional management and resources are adequate, curriculum relevance, practical communication skills, and collaboration with industry partners remain limited. The findings underscore the importance of revising curricula, enhancing teacher capabilities, and strengthening partnerships with Japanese employers to enhance employability outcomes. These implications extend to the broader development of Indonesia’s vocational education system, emphasising the need for responsive, industry-oriented training.